Effects of volatile organic compounds, damp, and other environmental exposures in the home on wheezing illness in children - Venn, A (BMJ Group, 2003)
Methods: Total volatile organic compounds, formaldehyde, nitrogen dioxide, damp (on a four category scale of % wood moisture equivalent), and environmental tobacco smoke (from salivary cotinine) were measured objectively in the homes of 193 children with persistent wheezing illness and 223 controls aged 9–11 years in Nottingham, UK. Results: The risk of wheezing illness was significantly increased only in relation to damp (odds ratio (OR) per increasing category=1.32 (95% confidence interval (CI), 1.00 to 1.75)), and was unrelated to the other exposures measured. Among cases, formaldehyde and damp were associated with more frequent nocturnal symptoms (OR per increasing quartile and category, respectively, 1.45 (1.06 to 1.98) and 1.97 (1.10 to 3.53)), significantly more so in atopic cases, but there was no effect of total volatile organic compounds, nitrogen dioxide, or cotinine. Conclusions: Domestic volatile organic compounds are not a major determinant of risk or severity of childhood wheezing illness, though formaldehyde may increase symptom severity. Indoor damp increases both the risk and severity of childhood wheezing illness.